La rappresentazione notturna della città - Chiavoni, Emanuela (2018)
The objective of the study is to investigate and experiment with the possibilities for the representation of cities during the night hours. The city and its cultural heritage are perceived both by citizens and tourists throughout the day and, above all, their appearance varies when they are invested by artificial light and not by natural light. In fact, light is always the main factor that determines the color changes. The places, the streets, the squares, the gardens, the buildings assume a different chromatic connotation and refer different spatial emotions to the observer, suggesting proposals for their valorization.